2001
DOI: 10.1006/eujc.2001.0499
|View full text |Cite
|
Sign up to set email alerts
|

A Result on Spreads of the Generalized QuadrangleT2(O), withOan Oval Arising from a Flock, and Applications

Abstract: If F is a flock of the quadratic cone K of PG(3, q), q even, then the corresponding generalized quadrangle S(F) of order (q 2 , q) has subquadrangles T 2 (O), with O an oval, of order q. We prove in a geometrical way that any such T 2 (O) has spreads S consisting of an element y ∈ O and the q 2 lines not in the plane PG(2, q) of O of q quadratic cones K x , x ∈ O − {y}, of the space PG(3, q) containing T 2 (O), where K x has vertex x, is tangent to PG(2, q) at x y and has nucleus line xn, with n the nucleus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Then S(F ) has at least q 3 +q 2 subquadrangles of order q; see Thas [16]. By Payne [8] any of these subquadrangles S$ is a T 2 (O) of Tits, with O an oval of PG (2, q).…”
Section: Subquadrangles and Ovoidsmentioning
confidence: 96%
“…Then S(F ) has at least q 3 +q 2 subquadrangles of order q; see Thas [16]. By Payne [8] any of these subquadrangles S$ is a T 2 (O) of Tits, with O an oval of PG (2, q).…”
Section: Subquadrangles and Ovoidsmentioning
confidence: 96%
“…In this section we add coordinates to the construction of Theorem 1.4 to show that the hyperoval completion of O is the same as the hyperoval constructed from an aflock by Cherowitzo and that the spread S of T 2 ðOÞ is the same as that constructed by Brown, O'Keefe, Payne, Penttila and Royle. Note that in [8] Thas showed that in the case of a flock of a quadratic cone that the q þ 1 (flock, axis to base oval of cone) pairs gave rise to the q þ 1 herd hyperovals constructed from a flock as formalised in Theorem 1.1.…”
Section: Algebraic Description Of O and Smentioning
confidence: 99%
“…In [3] the set of q þ 1 functions defining the hyperovals as above is called a herd. In [8] Thas gave a geometrical construction of these hyperovals from the flock (although not a geometrical proof of the construction).…”
Section: Introduction and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation